Virus-Specific Defense Responses in Sweetpotato: Transcriptomic Insights into Resistance and Susceptibility to SPFMV, SPCSV, and SPVD - Adero, J.; Ssali, R.T.; Segundo, F.; Maria, D.; Kitavi, M.; Yada, B.; Byarugaba, D.; Dube, F.; Aber, P.; Opiyo, S.; Fei, Z.; Kreuze, Jan F. (2025)
Sweetpotato (Ipomoea batatas L. Lam) production is threatened by complex viral diseases, notably sweet potato virus disease (SPVD) worldwide, which results from co-infection by sweet potato feathery mottle virus (SPFMV) and sweet potato chlorotic stunt virus (SPCSV). This study provides virus-specific transcriptomic insights into the immune responses of three sweetpotato cultivars, ‘Beauregard’, ‘Tanzania’, and ‘New Kawogo’, to SPFMV, SPCSV, and SPVD. Using RNA-seq profiling across three timepoints post-infection at 3, 6, and 12 weeks, we identified distinct virus- and genotype-specific gene expression responses. ‘New Kawogo’ activated early and sustained immune pathways involving redox regulation, transcriptional control, and hormonal signaling in response to both SPCSV and SPFMV, while showing minimal transcriptional disruption under SPVD, reflecting robust tolerance. ‘Beauregard’ exhibited early suppression of immune and metabolic genes, with delayed and disorganized recovery efforts, particularly under SPVD. Defense-related pathways including NBS-LRR signaling, RNA silencing, and hormonal regulation were consistently upregulated in ‘New Kawogo’ and to a lesser extent in ‘Tanzania’, but remained inactive in ‘Beauregard’. This study highlights candidate resistance and susceptibility genes for each virus, providing a molecular basis for developing virus-resilient sweetpotato cultivars through functional genomics and marker-assisted breeding. These findings elucidate the molecular basis of virus resistance in sweetpotato and identify candidate genes for marker-assisted breeding, despite limitations arising from the use of a diploid reference genome and discrete sampling intervals.